2014
DOI: 10.1016/j.pbb.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combining tactile with visual and spatial cues in conditioned place preference

Abstract: Previous research provides little information about variables that determine which elements of contextual cues gain associative control over behavior in the conditioned place preference (CPP) procedure. These studies examined the effect of external visual-spatial cues on CPP when tactile cues served as the conditioned stimuli. DBA/2J mice were trained in the dark (Experiment 1) or light (Experiment 2) using unbiased procedures in which the spatial location of an ethanol-paired tactile cue during training was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…3, 4, and 5), grid and hole floors were separated during conditioning by a clear acrylic divider placed in the center of the apparatus. Previous research in our lab shows no difference in the magnitude of ethanol-induced CPP produced by these configurations in DBA/2J mice trained in the dark (Cunningham and Zerizef, 2014). Moreover, given the variation in CPP procedures across laboratories, our inclusion of two common configurations allows for greater generality of our conclusions.…”
Section: Methodsmentioning
confidence: 59%
“…3, 4, and 5), grid and hole floors were separated during conditioning by a clear acrylic divider placed in the center of the apparatus. Previous research in our lab shows no difference in the magnitude of ethanol-induced CPP produced by these configurations in DBA/2J mice trained in the dark (Cunningham and Zerizef, 2014). Moreover, given the variation in CPP procedures across laboratories, our inclusion of two common configurations allows for greater generality of our conclusions.…”
Section: Methodsmentioning
confidence: 59%
“…Cunningham and Zerizef reported CPP from visual and spatial cues in the light or in the dark. 31) Further, Varela et al 32) reported that chronic complete light deprivation for 4 weeks inhibited appetitive associative learning induced by EtOH. Although methamphetamine and EtOH have very different mechanisms and subjective effects, a larger cage in which mice can move freely has been linked to greater methamphetamine-induced sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of those studies directly compared the specific cue configurations used here with ethanol, but a cross-experiment visual comparison of data reported by Cunningham and Zerizef (2014: Exps. 1 vs. 2) suggested no cue-configuration effect in D2 mice after four conditioning trials, an observation consistent with the results of Exp.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative tactile cues are isolated to different spatial locations only at the time of preference testing.This procedure contrasts with the more commonly used two-compartment (2C) procedure that exposes animals to spatially distinct portions of the apparatus that typically differ in their cue properties during conditioning trials. More thorough theoretical descriptions of differences between the 1C and 2C procedures can be found elsewhere (Cunningham et al 2006b; Cunningham and Zerizef 2014; Hitchcock et al 2014). …”
mentioning
confidence: 99%
See 1 more Smart Citation